Recognition of actuarial gains and losses under IAS 19 among UK Listed Companies - Nor Asma Lode; Napier, Christopher J. (Penerbit Universiti Kebangsaan Malaysia, 2014)
The requirement for UK listed companies to prepare their financial statements in accordance with IFRS for accounting periods beginning on or after January 1, 2005 provided these companies with an accounting policy choice in the area of pension accounting. Probit models indicate that the characteristics of size of firm and interest coverage are significant determinants influencing the choice of accounting policy. Therefore, managers are likely motivated to make the incomesmoothing accounting choice (the use of the “corridor” method) when size of firm and interest coverage are large, while the more volatile full recognition policy is more likely to be chosen when size of firm and interest coverage are small. These findings support the argument that the retention of options in IFRS may operate to the detriment of key stakeholders, in particular equity investors, by providing opportunities for earnings management.